PENULISAN KARYA TULIS ILMIAH BERBASIS PENELITIAN TINDAKAN KELAS - Nitta Puspitasari; Sukanto Sukandar Madio; Deddy Sofyan; Puji Lestari; Rostina Sundayana (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2018)
The importance of writing scientific paper based on Action Classroom Research for teachers in schools is the background why this training was carried out, given the number of teachers who make Action Classroom Research is still insignificant. Training carried out for 8 hours starts with a theoretical explanation of what Action Classroom Research is, how came up with an idea to create a Action Classroom Research and continued with assistance to the participants to create a classroom Action Classroom Research framework. The participants amounted to 13 people, consisting of middle and high school /vocational teachers in the Pameungpeuk area and its surroundings. The results showed that the teacher was able to analyze the problems in their respective schools to be used as a background in making a Action Classroom Research and also put forward a solution which later became the title of the Action Classroom Research. The results of this training can be used as a reference in carrying out the actual Action Classroom Research.